Divergent Expression of CXCR5 and CCR5 on CD4+ T Cells and the Paradoxical Accumulation of T Follicular Helper Cells during HIV Infection - Zaunders, John; Xu, Yin; Kent, Stephen J.; Koelsch, Kersten K.; Kelleher, Anthony D. (Frontiers in Immunology, 2017)
Viral infection sets in motion a cascade of immune responses, including both CXCR5+ CD4+ T follicular helper (Tfh) cells that regulate humoral immunity and CCR5+ CD4+ T cells that mediate cell-mediated immunity. In PBMC, the majority of memory CD4+ T cells appear to fall into either of these two lineages, CCR5-CXCR5+ or CCR5+CXCR5-. Very high titres of anti-HIV IgG antibodies are a hallmark of infection, strongly suggesting that there is significant HIV-specific CD4+ T cell help to HIV-specific B cells. We now know that characteristic increases in germinal centres (GC) in lymphoid tissue (LT) during SIV and HIV-1 infections are associated with an increase in CXCR5+PD-1high Tfh, which expand to a large proportion of memory CD4+ T cells in lymphoid tissue, and are presumably specific for SIV or HIV epitopes. Macaque Tfh normally express very little CCR5, yet are infected by CCR5-using SIV, which may occur mainly through infection of a subset of PD-1intermediate CCR5+Bcl-6+ pre-Tfh cells. In contrast, in human LT, a subset of PD-1high Tfh appear to express low levels of CCR5, as measured by flow cytometry, and this may also contribute to the high rate of infection of Tfh. Also, we have found, by assessing fine needle biopsies of LT, that increases in Tfh and GC B cells in HIV infection are not completely normalized by ART, suggesting a possible long lasting reservoir of infected Tfh. In contrast to the increase of CXCR5+ Tfh, there is no accumulation of proliferating CCR5+ CD4 T HIV Gag-specific cells in peripheral blood that make IFN-γ. Altogether, CXCR5+CCR5- CD4 T cells that regulate humoral immunity are allowed greater freedom to operate and expand during HIV-1 infection, but at the same time can contain HIV DNA at levels at least as high as in other CD4 subsets. We argue that early ART including a CCR5 blocker may directly reduce the infected Tfh reservoir in LT, and also interrupt cycles of antibody pressure driving virus mutation and additional GC responses to resulting neoantigens.